To Tube or Not to Tube? The Role of Intubation during Stroke Thrombectomy - Takahashi, Courtney; Liang, Conrad W.; Liebeskind, David S.; Hinman, Jason D. (Frontiers in Neurology, 2014)
In the 10 years since the FDA first cleared the use of endovascular devices for the treatment of acute stroke, definitive evidence that such therapy improves outcomes remains lacking. The decision to intubate patients undergoing stroke thrombectomy impacts multiple variables that may influence outcomes after stroke. Three main areas where intubation may deleteriously affect acute stroke management include the introduction of delays in revascularization, fluctuations in peri-procedural blood pressure, and hypocapnia, resulting in cerebral vasoconstriction. In this mini-review, we discuss the evidence supporting these limitations of intubation during stroke thrombectomy and encourage neurohospitalists, neurocritical care specialists, and neurointerventionalists to carefully consider the decision to intubate during thrombectomy and provide strategies to avoid potential complications associated with its use in acute stroke.